Transcranial direct-current stimulation over the primary motor cortex and cerebellum improves balance and shooting accuracy in elite ice hockey players - Zhang, N.; Nitsche, M. A.; Miao, Y.; Xiong, Z.; Vicario, C. M.; Qi, F. (International Journal of Sports Physiology and Performance, 2024)
Purpose To investigate the effects of transcranial direct-current stimulation (tDCS) applied over the primary motor cortex (M1) and cerebellum on balance control and shooting accuracy in elite ice hockey players.